Speed and direction of an obstacle using virtual window - Mohd Asri Mansor (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A virtual window is used to determine the direction and speed of a uniformly moving obstacle. Two intersections with the virtual window at different location are used to calculate the relative path and speed of the obstacle. Two simulations were performed using Excel 2010. The first simulation simulates a practical running of a uniformly moving obstacle, while the second has the obstacle moving at a very high speed. The result shows that the system was able to determine the relative speed and path of the uniformly moving obstacle accurately.